Potensi Ekstrak Daun Jambu Biji Sebagai Alternatif Inhibitor Korosi Besi untuk Pembelajaran Kimia Kontekstual - Shofrina Surya Dewi*; Retno Aliyatul Fikroh; Fuadatul Mukoningah (Universitas Syiah Kuala, 2022)
Contextual learning is a learning concept to connect learning materials and their function in daily life. The obstacle in implement contextual learning is the concept of learning that involves potential local resources. Guava leaf is one of the local resources that has many benefits and also contains tannins, which have potential as an ingredient corrosion inhibitor base. This study aims to analyze core competence, basic competence, and competency indicator of corrosion material, the results of making guava leaf extract as inhibitor corrosion for contextual learning, and extract potential guava leaves as a natural corrosion inhibitor. This study employs descriptive qualitative research, the methods used include literature study, observation, experimentation, and interviews. The results of this study show that the relationship between corrosion materials and experiment is the identification of factors that can prevent corrosion, explanation of ideas to prevent corrosion, comparisons of the fast and slow corrosion process, and corrosion rate analysis. This experiment was carried out by modifying tools, materials, and methods of work. Maceration method using 70% ethanol as solvent. The results of the Corrosion rate showed that increasing the concentration of inhibitor then lowers the corrosion value obtained. In this study, the highest corrosion rate occurred on iron with a 0% inhibitor concentration is 0,00175 g/cm2.days, while the lowest corrosion rate occurred on iron with 20% inhibitor concentration, is 0,00025 g/cm2.day. Based on the analysis, natural inhibitors of extract Guava leaf can be used as a simple experiment alternative in school.